Tata Negara dan Peradaban Islam: Antara Cita-cita dan Ilusi - Alfathri Adlin (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2016)
All circles of Moslem communities have intendedto revive Islam as a prominent civilization, after lagging behind the West civilization for long period. Yet, while some Islamist-fundamentalists made efforts for that by way of politics, Islam sometimes was stereotyped with its rigorous face among both non-Moslems as well as Moslems whose religious thought and scientific/philosophical discourse was regarded as conflicted with Islam . Meanwhile, both political Islam and fundamentalist orthodoxies, and various autocracy and quasi-democracy that rules in Islamic World were and stillconcerned more with outward models of religious piety and obedience aimed at confirming that Islamic govermentality does exist in their society. Unfortunately, the imposing of outward norms and rules can not become a stage for retrieving the inward ethics or Islamic spiritual dimension, from which the drive for a new civilization could emerge as ever did in and was realized by Islam Nusantara in its early formation by the Saints and Sufis. Unless the Moslems are able to gather the inward resources of their religion to produce its outward presence of civilizational power, they—reformistor fundamentalist—willbe forced to participate and dissolve in the dominant western civilizational order which has given up to a secularization process. Here they are faced to the dilemma between the need to preserve the moral equilibrium in themselves as demanded by Islam and success requirements as demanded by modern world. And it is this that has resulted in a cultural schizophrenia among the Moslems from all the circles.